An analysis of the completion of physiotherapy clinical records in Gauteng Province. - V. R. P. M'kumbuzi; C. J. Eales; A. Stewart (AOSIS, 2002)
The purpose of this study was to rate the completion of physiotherapy assessment, treatment and progress records in the Gauteng province of South Africa. There is a dearth of literature on physiotherapy patient records, yet it has been demonstrated that clinical records have significant implications for quality of care, resource allocation, research and for professional litigation. A combined retrospective and prospective research design, using a quality assurance instrument was used to rate the completeness of physiotherapy records obtained from multiple study sites. Breakdown in clinical recording in the following areas is described: • areas of care (private and public sectors), • patient conditions (e.g. orthopaedic and surgical) • patient categories (in and out patients), • section of the record (e.g. demographics, physical examination), and • providers of care (physiotherapists, physiotherapy assistants and physiotherapy students). The 644 records analyzed scored a mean overall completion rate of 64%. There was a significant difference observed in overall record completion (p = 0.0004) between private and public sector providers. Significant differences were also observed for each section of the record. Factors most associated with a high degree of completion of physiotherapy patient records included; private sector physiotherapy services, use of pre-formatted assessment charts and clinicians' participation in relevant continuing education. Physiotherapy patient records in Gauteng were found to be incomplete. The implications of this finding in an increasingly competitive global, national, corporate and domestic healthcare arena include; physiotherapy service quality, professional litigation, resource allocation and policy development, as well as professional growth, development and satisfaction with ones' career. Recommendations on how the physiotherapy profession can improve clinical recording from an educational, clinical and managerial perspective are suggested.